(3TQM Ydi QSGdI GdSeQbfOi aj GdGSJYGQGJs - (3YHO Gddg Hf Ydj GdOedjLi GdCRHcGhi (B( (3GdCRHci (B) (3GdTGaYj GdedbH HShjOGfs; (3GdSeQbfOjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg QH GdYGdejf agPG TQM dWja Ydi QSGdI GdEeGe GdSeQbfOi ai GdGSJYGQGJ HSe Gddg GdQMef GdQMje GdMeO dhGgH GdYWjI Ci eYWjgG s
(3BNQgG (B:s
(3agi JQTjN ddeLGR GdYbdi heG ShGg JQTjM Ch Cf eG jMbbgG heG ShGg JQTjM hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3HdGZgs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs